Study of Epidemiological Aspects of Cholera in the Edea Health District, Littoral–Cameroon (London Journal of Medical and Health Research, 2025)
Introduction: Cholera is an acute diarrhoeal disease caused by infection of the intestine with Vibrio cholerae type O1 or O139 bacteria, which can lead to rapid dehydration and death. Both children and adults can be infected. Cholera is closely associated with poverty, poor sanitation and the absence of safe drinking water. As a result, the burden of cholera is concentrated in Africa and South Asia, accounting for around 99% of cases worldwide. Against a backdrop of water shortages in the town of Edea, and following confirmation of the existence of an outbreak of cholera in the town, a number of investigations were carried out to describe the event in terms of time, place and people, and to put control measures in place. The aim of this article is to report on the cholera epidemic observed in the Edea health district with a view to strengthening disease surveillance.Methods: We conducted a descriptive cross-sectional study from the 1st to the 52nd epidemiological week of 2022 in the Edea health district, Littoral region, Cameroon. A linear list was drawn up, and cases were actively sought in the consultation registers of the health facilities and in the community. All suspected cholera cases notified in the health areas of the Edea health district were included in this study. Demographic, clinical, origin and outcome variables were extracted from the linear cholera list of the Edea Health District and analysed using EasyMedStat (version 3.22) and Microsoft Excel 2016.Results: A total of 34 suspected cholera cases were identified in the district, including 2 deaths (5.88%). Of the suspected cases, 10 were RDT positive and 1 was confirmed by culture (V. cholerae O1 or O139); all over a period of 52 epidemiological weeks in 2022. The sex ratio F/M was 1.61. All age groups were affected. The most common age group was ?15 years, with 28 cases (82.3%). Most of the cases came from the Malimba health area: 9 cases (26.4%). All cases presented with diarrhoea and vomiting. Moderate dehydration was most frequently observed: 14 cases (41%).Conclusion: A cholera epidemic has been confirmed in the Edea Health District. In order to contain future epidemics and move towards the elimination of the disease, it is essential to strengthen epidemiological surveillance and the application of preventive measures against cholera in the district, particularly during the rainy season, and to promote multi-sectoral collaboration through the involvement of all stakeholders in related sectors.
Keywords: epidemic; Cameroon; Cholera; Edea